Large amplitude solitary hole in relativistic electron beam - Lapshin, V.I.; Maslov, V.I.; Tkachenko, I.V. (Вопросы атомной науки и техники, 1999)
The possibility to excite the coherent solitary wave structure like the electric potential hump of large amplitude in the accelerator electron beam has been considered. Its properties and dependencies of properties on amplitude have been investigated.